(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the pragmatic problems in translation, with a focus on achieving pragmatic adequacy between the original and the translated text. The article discusses various challenges, including genre characteristics, background knowledge of the intended reader, communicative purpose, and sociolinguistic factors. Pragmatic adequacy is defined as a translation that fully reflects the original, emphasizing the importance of maintaining linguistic norms and rules. The study delves into the role of dialects, modernization, and other factors in ensuring pragmatic adequacy. The article addresses the challenges posed by regional dialects in translation, emphasizing the loss of pragmatic features when elements specific to dialects are not translated.